Fibrinogen induces inflammatory responses via the immune activating receptor LILRA2 - Li, Yifan; Hirayasu, Kouyuki; Hasegawa, Gen; Tomita, Yosei; Hashikawa, Yuko; Hiwa, Ryosuke; Arase, Hisashi; Hanayama, Rikinari (Frontiers in Immunology, 2024)
The leukocyte immunoglobulin-like receptor (LILR) family, a group of primate-specific immunoreceptors, is widely expressed on most immune cells and regulates immune responses through interactions with various ligands. The inhibitory type, LILRB, has been extensively studied, and many ligands, such as HLA class I, have been identified. However, the activating type, LILRA, is less understood. We have previously identified microbially cleaved immunoglobulin as a non-selfligand for LILRA2. In this study, we identified fibrinogen as an endogenous ligand for LILRA2 using mass spectrometry. Although human plasma contains fibrinogen in abundance in its soluble form, LILRA2 only recognizes solid-phase fibrinogen. In addition to the activating LILRA2, fibrinogen was also recognized by the inhibitory LILRB2 and by soluble LILRA3. In contrast, fibrin was recognized by LILRB2 and LILRA3, but not by LILRA2. Moreover, LILRA3 bound more strongly to fibrin than to fibrinogen and blocked the LILRB2-fibrinogen/fibrin interaction. These results suggest that morphological changes in fibrinogen determine whether activating or inhibitory immune responses are induced. Upon recognizing solid-phase fibrinogen, LILRA2 activated human primary monocytes and promoted the expression of various inflammation-related genes, such as chemokines, as revealed by RNA-seq analysis. A blocking antibody against LILRA2 completely inhibited the fibrinogen-induced inflammatory responses, indicating that LILRA2 is the primary receptor of fibrinogen. Taken together, our findings suggest that solid-phase fibrinogen is an inflammation-inducing endogenous ligand for LILRA2, and this interaction may represent a novel therapeutic target for inflammatory diseases.